2018
DOI: 10.2478/auoc-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Toxicants and Biomarkers of Oxidative Stress in Samples from Ebubu and Elele-Alimini Communities in Rivers State

Abstract: Abstract. This study was carried out to assess the levels of heavy metals, polycyclic aromatic hydrocarbons (PAHs), and antioxidants present in pumpkin leaf (Telfairia occidentalis), catfish (Clarias anguillarus), and African land snail (Archachatina marginata), obtained from Ebubu and Elele-Alimini communities in Rivers State, Nigeria. The heavy metals and PAHs were analyzed using Atomic Absorption Spectrophotometry (AAS) and gas chromatography respectively, while the antioxidants were assayed by conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(13 reference statements)
1
4
1
Order By: Relevance
“…Amadi et al, 70 posited that elevated MDA levels are suggestive of depleted antioxidant enzyme systems, implying that C. portoricensis, D. arborea, D. repens, P. juniperinum, and P. caperata may have induced oxidative stress in the experimental animals. Further, in agreement with the observations of Ogunka-Nnoka et al, 71 and Ogunka-Nnoka et al, 72 the reductions in levels of SOD, CAT, GSH, and GPx indicated the presence of toxic substances in the plant extracts, which may have suppressed their activities. Maintenance of intracellular levels of GST and GR is of paramount importance for removal of xenobiotics from the system.…”
Section: Grpsupporting
confidence: 91%
“…Amadi et al, 70 posited that elevated MDA levels are suggestive of depleted antioxidant enzyme systems, implying that C. portoricensis, D. arborea, D. repens, P. juniperinum, and P. caperata may have induced oxidative stress in the experimental animals. Further, in agreement with the observations of Ogunka-Nnoka et al, 71 and Ogunka-Nnoka et al, 72 the reductions in levels of SOD, CAT, GSH, and GPx indicated the presence of toxic substances in the plant extracts, which may have suppressed their activities. Maintenance of intracellular levels of GST and GR is of paramount importance for removal of xenobiotics from the system.…”
Section: Grpsupporting
confidence: 91%
“…Low nickel contamination was observed in OMV, NMV and MMY. However there was moderate nickel contamination in NMAV and AMY, but lower than the reports of Ogunka-nnoka et al 33 There was also moderate mercury in OMV, NMV, and NMAV whereas there was low contamination at MMY and AMY. There was moderate silver contamination in MMY and with arsenic in NMV and AMY.…”
Section: Resultscontrasting
confidence: 67%
“…They indirectly protect cells against the adverse effects of xenobiotics, carcinogens and toxic radicals (Griffith, 1999). Lipid peroxidation has been suggested to play a role in metal toxicity, with numerous studies undertaken using malondialdehyde (MDA) as biomarker of oxidative stress (Steven and Nerishi, 1992;Khalil, 2015 andOgunka-Nnoka et al, 2018).…”
Section: Discussionmentioning
confidence: 99%